(untitled) (LACCEI, 2024)
Population growth, access to services to achieve a better quality of life, access to employment and other factors have led to rapid urbanization in inadequate and overburdened sites in Latin American countries. The 2030 agenda aims to achieve sustainable cities and communities that offer comfort and safety based on construction and planning requirements in line with regional and national development. This motivated the study of a population center in the Peruvian jungle, carrying out a geotechnical zoning of soils based on their chemical, physical and mechanical properties. Twelve test pits were made and strategically distributed in the study area according to the technical requirements of the E050 standard for Soils and Foundations. This was complemented by six types of laboratory tests, the most important being the Direct Shear and Modified Proctor tests. From these the soil types were obtained: low and high plasticity clayey soils (CL and CH) and low and high plasticity silty soils (ML and MH). With the standard proctor test it was determined that its maximum density is within the range of 1.598 to 1.933, as well as, with the direct cut test it was determined that they exceed the minimum normative value of 0.50kg/cm2 and with respect to the analysis of soluble salts it was verified that there is a minimum percentage of salinity. Soil zoning maps were prepared. It was concluded that the study area in the Selva Alta del Perú is suitable for constructions of no more than three stories, and because of its low salinity, "Portland type I" cement can be used as a construction material. Translated with www.DeepL.com/Translator (free version)